Adaptable MBSE Problem Definition with ARMADE: Perspectives from Firefighting and AAM SoS Environments - Adrian Chojnacki; Giuseppa Donelli; Luca Boggero; Prajwal S. Prakasha; Björn Nagel (Engineering Proceedings)
Model-based systems engineering (MBSE) offers significant advantages over traditional document-based approaches, particularly in improving the clarity, traceability, and efficiency of requirements engineering (RE). However, MBSE also introduces challenges, particularly in maintaining consistent semantics and handling evolving system models. This paper presents ARMADE, an agile requirements management and definition environment developed at DLR, which aims to address these challenges. ARMADE enables the flexible, user-friendly modeling of system requirements using a data model that incorporates natural language patterns. The tool supports the dynamic adaptation of metamodels and facilitates collaborative, project-wide requirements management. A case study based on two systems of systems (SoS) from the EU-funded HE COLOSSUS project—firefighting and advanced aerial mobility (AAM)—demonstrates ARMADE’s ability to manage complex, interdisciplinary requirements. The study highlights the tool’s potential to reduce data inconsistencies, improve adaptability, and enhance the overall efficiency of the RE process. By enabling seamless updates and changes to requirements, ARMADE shows promise as a versatile solution for dynamic metamodeling in complex systems, with potential applications extending beyond aeronautics to various industries reliant on intricate requirements management.